Parametric Updating of Steel Strand Stay Cable Force Calculation Model Based on Response Surface Method - Shizhan Xu; Yinggang Ma; Hao Zhang (Advances in Civil Engineering)
In order to solve the problem that the calculation result of cable force deviates from the measured value because the parameters of steel strand stay cable are not exactly equal to the designed value in practical engineering, a model updating method selecting the steel strand stay cable parameters as the updating parameters and using more measured data as the objective function was proposed. This method selects the central composite design in the response surface method. In the fine-fitting model affected by the cross-term and high-order terms between parameters, the value of the parameter to be corrected is optimized according to the measured data. Using the above method, taking a cable-stayed bridge without a backstay as the engineering background, the model updating is carried out by using the cable force monitoring data during the construction monitoring process. The results show that using this method, the updated values of the parameters of the cable can be obtained according to the measured data, and the updated values of the parameters are consistent with the reality. The deviation between the calculated value of cable force and the actual cable tension obtained according to the parameter updating decreases significantly, and most of the deviation is reduced from 30% to 50% before the updating to less than 5%. The updating effect is obvious and meets the engineering requirements.